Retailing Amidst Information Technology - Catalino N. Mendoza (Zien Journals, 2021)
With the increasing globalization of retailing, both in terms of their points-of-sale and their points-of-supply; the information technology (IT) spend in the retail sector has increased significantly. IT plays an increasingly important role in the management of complex retail operations. Market knowledge, as well as control of data and information, is key to obtaining a competitive advantage in the retail sector. Markets are continuing to grow and become more complex; the simple process of retailing has started to deploy more advanced retail information systems to cope with all the transactions involved. Today, retailers need to transform their IT capabilities for multiple reasons, including: • To increase the company’s ability to respond to the evolving marketplace through enhanced speed and flexibility. • To collect and analyze customer data while enhancing differentiation. • To work effectively; retailers need one system working across stores (or even across national borders) to make sure the most effective use of stock and improve business processes. Retailers are beginning to notice that technology’s role is one of an enabler. Essentially, information technology can speed up processes and deliver cost saving benefits to the company.
Keywords: Retail industry; Market knowledge; Technology’s role; IT management